Evaluation methods of α and β2-adrenoreactivity of human erythrocytes to change their osmotic resistance under the effect of adrenaline and adrenoblockers - Voloh, F. O. (Journal of Education, Health and Sport, 2017)
According to the data of literature the main evaluation methods of α and β2-adrenoreactivity of human erythrocytes have been described to change their osmotic resistance under the effect of adrenaline and blockers. Nowadays β-blockers are used in many cardiac diseases to prevent sudden cardiac death. They are acute coronary syndromes, chronic coronary heart disease (CHD), arterial hypertension (AH), arrhythmias, congestive heart failure (CHF), hypertrophic cardiomyopathy, mitral valve prolapse. β-blockers are also used in such diseases and syndromes as migraine, glaucoma, thyrotoxicosis. The article presents the results of a study of evaluation methods to identify functional changes, diagnosis and prognosis of chronic cerebral ischemia of hypertensive genesis of different stages. That’s why the author applied a complex approach. It based primarily on the fact of inhibition of hemolysis of erythrocytes placed in the hyposmotic medium in the presence of beta-blocker, on visual fixation of the change of erythrocyte aggregation under the effect of adrenaline and other adrenergic agents, and on the registration of changes in osmotic resistance of erythrocytes under the influence of β-adrenoblockers. According to the results the indicators of these methods of evaluation of beta-adrenoreactivity allow to differentiate the stages of the disease at the cellular level quickly and reliably. They depend on the physiological state and patients’ sex. The indicators can also be an objective criterion for assessing the effectiveness of treatment and optimize approaches to prevent progression of cerebral circulation disorders.